To rewrite \( 3^{\sqrt{189}} \) as the product of an integer and another irrational cube root, we first simplify \( \sqrt{189} \).
Step 1: Simplify \( \sqrt{189} \)
We can factor \( 189 \) as follows: \[ 189 = 9 \times 21 = 3^2 \times 21 \]
Next, we can take the square root: \[ \sqrt{189} = \sqrt{9 \times 21} = \sqrt{9} \times \sqrt{21} = 3\sqrt{21} \]
Step 2: Substitute back into the original expression
Now substituting \( \sqrt{189} \) back into the expression we have: \[ 3^{\sqrt{189}} = 3^{3\sqrt{21}} \]
Step 3: Rewrite the expression using properties of exponents
Using the property of exponents, \( a^{m \cdot n} = (a^m)^n \), we can rewrite \( 3^{3\sqrt{21}} \): \[ 3^{3\sqrt{21}} = (3^3)^{\sqrt{21}} = 27^{\sqrt{21}} \]
Step 4: Express as a product of an integer and another cube root
Using the fact that \( 27 = 3^3 \), we can express this in the form requested: \[ 3^{3\sqrt{21}} = 27 \cdot 3^{0} \cdot 27^{\sqrt{21}} = 27 \cdot (3^{\sqrt{21}})^{3} \]
But there's a more straightforward approach: Recall that: \[ 3^{\sqrt{189}} = 27 \cdot 3^{\sqrt{21}} \]
Final expression in product form: \[ 3^{\sqrt{189}} = 27 \cdot 3^{\sqrt{21}} \]
Conclusion
Thus, \( 3^{\sqrt{189}} \) can be expressed as: \[ 27 \cdot 3^{\sqrt{21}} \]
In terms of the cube root format, \( 3^{\sqrt{21}} \) is irrational. Hence, you can express \( 3^{\sqrt{189}} \) as: \[ 3^{\sqrt{189}} = 27 \cdot \sqrt[3]{3^{\sqrt{21}}} \]